Rotation at subduction margins: How complexity at fault‐scale (the 2019 Albanian Mw 6.4 earthquake) mirrors the regional deformation. (28th February 2022) - Pezzo, Giuseppe; Palano, Mimmo; Chiarabba, Claudio
Abstract: A variety of tectonic processes spread along the circum‐Mediterranean orogenic belts driven by the convergence of major plates, episodes of slab retreat and lateral and vertical mantle flows. Here, we provide an updated view of crustal stress and strain‐rate fields for the Albanides belt in the eastern Adria‐Eurasia convergence boundary. We framed a new geodetic‐based source model for the 2019 Mw 6.4 Durrёs earthquake in light of the regional deformation, propending for a transpressional west‐dipping seismogenic fault. Our results highlight a fault‐scale complexity which mirrors the long‐time scale deformation of the Albanides plate boundary, where the rotation induced by the fast Hellenic rollback is accommodated also by transpression on inherited structures.